Colocalization of vitiligo and lichen planus in a patient with autoimmune thyroiditis - Veller-Fornasa, C... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
A case of a 63 years old woman with autoimmune thyroiditis and the presence ofpapules of lichen planus strictly within pre-existing depigmented areas of vitiligo is described. To the art of our knowledge there are no case like thispreviously published in the literature.
Keywords: Lichen Planus; Lihen planus; Middle Age; Srednja leta; Thyroiditis, Autoimmune; Tiroiditis avtoimuski; Vitiligo